Beyond Fulfilment To Intergenerational Research In Higher Education: Bridging Generational Expertise Through African-Inspired Indigenous Knowledge Exchange Systems - Zishiri, Christopher; Samkange, Wellington; Jim, Ottiliah (CV. Inara, 2025)
Higher education institutions are increasingly influenced by neoliberal paradigms that emphasise individual career fulfillment, measurable outcomes, and short-term gains in research. Based on socio-cultural theory and critical pedagogy, this study critiques this trend, arguing that it limits collaborative opportunities for intergenerational research (IGR) and contributes to epistemic fragmentation. A significant gap remains in how student research is conducted, with undergraduate and master's projects often reduced to mere requirements for degree completion rather than opportunities for developing authentic research skills applicable to real-world contexts. The paper contends that the intergenerational transfer of research skills is crucial for sustainable research practices in higher education. This study explores how knowledge from established researchers can be combined with digitally proficient novice researchers to promote intergenerational research stewardship within higher education. Using a mixed-methods approach, the study involved 100 participants comprising 20 academic staff, 50 undergraduates, and 30 master's students from five Zimbabwean universities. The findings reveal systemic barriers to IGR, such as rigid academic hierarchies, research supervision illiteracy, and institutional neglect. The research highlights opportunities for fostering IGR skills through ethical mentorship and collaborative strategies modeled on African Knowledge Transmission and Preservation Systems (AKTPS). The study advocates for transformative IGR models and recommends a paradigm shift from research frameworks that focus on lean fulfillment purposes to collaborative models, positioning IGR as a cornerstone for research skills transfer from expert to novice researchers.